Genome-Wide Analysis of β-Galactosidases in Xanthomonas campestris pv. campestris 8004 - Wang, Huiqi; Shi, Chenyi; Xie, Qingbiao; Wang, Yaxin; Liu, Shiyao; Li, Chunxia; He, Chaozu; Tao, Jun (Frontiers in Microbiology, 2018)
Bacterial β-galactosidase is involved in lactose metabolism and acts as a prevalent reporter enzyme used in studying the activities of prokaryotic and eukaryotic promoters. Xanthomonas campestris pv. campestris (Xcc) is the pathogen of black rot disease in crucifers. β-Galactosidase activity can be detected in Xcc culture, which makes Escherichia coli LacZ unable to be used as a reporter enzyme in Xcc. To systemically understand the β-galactosidase in Xcc and construct a β-galactosidase-deficient strain for promoter activity analysis using LacZ as a reporter, we here analyzed the putative β-galactosidases in Xcc 8004. As glycosyl hydrolase (GH) family 2 (GH2) and 35 (GH35) family enzymes were reported to have beta-galactosidase activities, we studied all of them encoded by Xcc 8004. When expressed in E. coli, only two of the enzymes, XC1214 and XC2985, were found to have β-galactosidase activity. When deleted from the Xcc 8004 genome, only the XC1214 mutant had no β-galactosidase activity, and other GH2 and GH35 gene deletions resulted in no significant reduction in β-galactosidase activity. Therefore, XC1214 is the main β-galactosidase in Xcc 8004. Notably, we have constructed a β-galactosidase-free strain that can be employed in gene traps using LacZ as a reporter in Xcc. The results reported herein should facilitate the development of high-capacity screening assays that utilize the LacZ reporter system in Xcc.